Slum Real Estate: The Low-Quality High-Price Puzzle in Nairobi's Slum Rental Market and Its Implications for Theory and Practice - Gulyani, Sumila; Talukdar, Debabrata (2012)
This study of 1,755 households in Nairobi's slums challenges the conventional belief that slums offer low-quality, low-cost shelter to a population that cannot afford better standards. In Nairobi, slums provide low-quality but high-cost shelter. Although slum residents pay millions of dollars in rents annually, and better quality units command higher rents, very little is being re-invested to upgrade quality. To resolve the challenge that the Nairobi puzzle poses for theory and practice, we develop a new analytical framework for understanding quality of living conditions. Improving conditions in Nairobi's slums requires, we argue, two simultaneous interventions: alteration of the tenure mix to enhance owner occupancy and infrastructure investment.